2006
DOI: 10.1590/s0100-69912006000200003
|View full text |Cite
|
Sign up to set email alerts
|

Estudo do reparo do ferimento de colon com o lado seroso da parede de jejuno, utilizando cianoacrilato e cola de fibrina

Abstract: RESUMO: Objetivo:Comparar o efeito do cianoacrilato e da cola de fibrina como adesivo das bordas do ferimento de cólon reparado com o lado seroso da parede de jejuno. Método: Foram utilizados 45 ratos wistar adultos jovens, machos , com peso médio de 260 gramas procedentes do Biotério Central da Universidade Estadual de Maringá.Os animais foram submetidos a procedimento operatório sob sedação com thiopental para produção de ferimento pradonizado de 0,5 cm distante caudalmente a 2 cm do ceco que foi reparado no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
3
0
1
Order By: Relevance
“…. Serosal patching has being described as a well succeeded supplemental technique when employed to different organs and species 1,5,8,[10][11][12][13][14][15][16][18][19][20] . However, one study showed that the use of a serosal patch over intestinal anastomosis did not increase the survival of dogs with peritonitis, when compared to individuals that did not receive such supplementation 15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…. Serosal patching has being described as a well succeeded supplemental technique when employed to different organs and species 1,5,8,[10][11][12][13][14][15][16][18][19][20] . However, one study showed that the use of a serosal patch over intestinal anastomosis did not increase the survival of dogs with peritonitis, when compared to individuals that did not receive such supplementation 15 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, mesothelial cells and vessels from the serosa provide healing support to the diseased tissue 9 . Serosal patching has being described as a supplemental technique for the correction of abdominal and caudal thoracic esophageal defects 10,11 ; however, it has being mainly recommended in intestinal diseases [12][13][14] . In one study, the use of a serosal patch over intestinal anastomosis did not increase the survival of dogs with peritonitis, when compared to individuals that did not receive such supplementation 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Vários autores utilizaram-na como complemento em suturas do intestino delgado 5,10,17 e grosso 8,9,17 , com resultados conflitantes quanto à sua eficiência na proteção das anastomoses. Outros autores utilizaram-no como proteção em situações adversas para a feitura da anastomose [18][19][20] .…”
Section: Discussionunclassified
“…The guinea pigs stayed in the animal colony for 30 days prior to the experiment for acclimation and observation. They were kept in cages and received Nuvital chow and water ad libitum [ 8 ] . The animals were randomly allocated into three groups of eight animals each [ 9 ] : group I (control), group II (polyurethane), and group III (cyanoacrylate).…”
Section: Methodsmentioning
confidence: 99%